1991
DOI: 10.1177/074823379100700401
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Exposure/ Pharmacokinetic Based Approach to the Assessment of Complex Exposures

Abstract: A problem in evaluating the hazard represented by an environmental toxicant is that exposures can occur via multiple media such as water, land, and air. Lead is one of the toxicants of concern that has been associated with adverse effects on heme metabolism, serum vitamin D levels, and the mental and physical development of infants and children exposed at very low environmental levels. Effects of lead on development are particularly disturbing in that the consequences of early delays or deficits in physical or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The impact of low-level lead exposure on children 's development has been a matter of discussion for some time [11]. Recent meta-analysis supports the conclusion that low-level lead exposure has a measurable, although small effect on children's IQ [3,4,12].…”
Section: Discussionmentioning
confidence: 95%
“…The impact of low-level lead exposure on children 's development has been a matter of discussion for some time [11]. Recent meta-analysis supports the conclusion that low-level lead exposure has a measurable, although small effect on children's IQ [3,4,12].…”
Section: Discussionmentioning
confidence: 95%
“…A house lead dust concentration standard of 1000 mg kg -1 was proposed by Laxen [7]. The correlation between measured dust and blood lead was reviewed by Derosa et al [8] and concluded that for each increase of 1000 ppm of lead in dust, the blood lead increased by 0.2 to 7.2 g dl -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Scholars began to study heavy metals in the 1980s and 1990s. DeRosa (1991) assessed the effects of lead, an environmental poison, on children's physical or intellectual development. Before 2000, the research focused on the spatial distribution and pollution assessment of heavy metal pollution.…”
Section: Introductionmentioning
confidence: 99%